Bodyweight Measures and Lifestyle Habits in Individuals with Multiple Sclerosis and Moderate to Severe Disability - Livne-Margolin, Moran (J Clin Med, 2021)
Multiple sclerosis (MS) is a chronic disease marked by progressive disability and decreased mobility over time. We studied whether individuals with MS of higher disability levels will be more overweight/obese as a result of their immobility and/or recurrent steroid treatments. In a prospective study, 130 individuals with MS and significant disability were classified according to the Expanded Disability Status Scale (EDSS) score as belonging to four groups: EDSS 3.0–4.0 (n = 31, 24%), EDSS 4.5–5.5 (n = 24, 18%), EDSS = 6.0 (n = 44, 34%) and EDSS ≥ 6.5 (n = 31, 24%). Medical history, body mass index (BMI), waist circumference and the level of engagement in physical activity were obtained. The mean ± standard error age was 55.8 ± 0.5 years, disease duration 18.2 ± 1.0 years and EDSS score 5.5 ± 0.1. Disease duration, the number of steroid courses per disease duration, weight, BMI and physical activity did not differ according to the four disability groups. The mean waist circumference increased significantly with increased severity of EDSS, p = 0.03. Increased disability in individuals with MS was not correlated with disease duration, lifestyle habits or overweight/obesity. However, increased disability was associated with central obesity.